Treatment satisfaction among diabetics attending a tertiary care hospital of Rohtak, Haryana: a cross-sectional study - Rajput, Meena; Arivarasan, Yashodha; Rajput, Rajesh; Khongsit, Aereosonova (International Journal Of Community Medicine And Public Health, 2019)
Background: The epidemic of diabetes mellitus is rising globally due to urbanization, population growth, aging, obesity and sedentary life style. Treatment satisfaction is defined as the individual’s rating of important attributes of the process and outcomes of his/her treatment experience and it represents an important outcome as it is related to adherence and willingness to continue treatment. Methods: A cross-sectional descriptive hospital-based study was conducted at endocrinology OPD attached to Pt. B.D. Sharma PGIMS Rohtak, Haryana from May 2014 to April 2015. Five hundred diabetics (type 1 and 2) were recruited for the study. Patients registered on the day of interview were selected using systematic random sampling. A predesigned, pretested, semi-structured schedule which included socio-demographic variables of the study subjects along with information about family history of diabetes was filled by interviewing the study subjects in their vernacular language individually. DiabMedSat was used to assess the treatment satisfaction. Results: Nearly two third of the study participants were treated on oral hypoglycaemic agents (76.2%) followed by subjects treated on insulin+OHA (21.4%). 2.4% of the study subjects were on treatment with insulin alone. 87.8% of female subjects were satisfied with their treatment as compared to 86.3% of their male counterparts. Conclusions: Treatment satisfaction has a positive influence on quality of life of the study subjects as those who are satisfied tend to better adhere to their drug regimen thereby achieving a desirable glycaemic control and averting the complications associated with the disease thereby leading to a healthier life.